Penerapan Metode Rapid Aplication Development (RAD) pada Pengembangan Sistem Informasi Inventaris Aset Desa Rempoah - Eva Argarini Pratama; Sinta Krisgianti; Hanny Mitya Paramita (Infotek: Jurnal Informatika dan Teknologi, 2023)
Village assets are managed based on public interest, convenience, legal certainty, transparency, economy, effectiveness, accountability, and value security. The process of managing village asset inventory sometimes still uses process stages that actually have negative impacts such as recording and updating village asset data which is so large and always up to date quickly, as well as the need for information disclosure related to these village assets, it is necessary to develop an information system that can utilized and assist in the management process. The information system that will be developed using the Rapid Application Development (RAD) method is expected to be an alternative solution to village asset inventory management problems. In this information system there are two main users, namely village officials and village heads. Village officials as well as administrators can manage matters related to village assets and village heads have the convenience of receiving output from the village asset inventory system for future management policy making